A Study on Habit of Reading Newspapers in Surkhet District of Nepal - Rai, Rashmi (Journal of Contemporary Review, 2024)
The searcher study entitled "A Study on Habit of Reading Newspapers" was carried out to find out the students and teachers' habit of reading newspapers of in Surkhet valley. The total Sample size of the study population was 108 with 90 students and 18 teachers. They were taken from both private and government aided school. Students were selected randomly and teachers were selected Purposive sampling. The researcher found that they had habit of reading newspapers for language learning, enrich vocabularies, learning sentence structure, learning grammar, learning communicative function and increase creative thinking power. It was also found that private schools students read newspapers more than government aided school's students. Private school's students were self-encouraged by teacher and friends for reading newspapers. It was also found that both governments aided schools and private school's teachers equally had habit of reading newspapers. Private school's teachers read newspapers for information but government aided school's teachers read for language development.